(3YbhO GdCTZGd GdOhdjI (B: s (3OQGSI ebGQfI (B/ s - (3Ydj eQVj YjGT GdYfRjs; (3LGHQ LGO fUGQ (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2009)
(3GdYbO(B: (3YeheG gh JhGab EQGOJjf Ydi EMOGK CKQ bGfhfj eYjf(B: (3jJeKd aj GdJRGe TNU Ch CcKQ aj ehGLgI TNU BNQ Ch CcKQ(B: (3HEYWGA TiA Ch GdbjGe HYed Ch GdGeJfGY Yf Yed(B: (3h EPG cGf GdYbO jdYH aj GdbGfhf GdOGNdi OhQG CSGSjG aj JHGOd h JOGhd GdKQhGJ h GdNOeGJ aEf Pdc GdOhQ jJYGXe aj GdbGfhf GdOhdj ddCaQGO(B. (3h YGOI eG JdLC GdOhdI Edi GdGSJYGfI HQDhS GdCehGd GdCLfHjI(B: (3dSO GdfbU GdPj JYGfj efg aj GdchGOQ GdafjI(B: (3h CSGdjH GdUfGYI GdMOjKI(B: (3h GdJbfjGJ GdeJWhQI(B: (3Ch ddMUhd Ydi eG jJeJY Hg GdWQa GdCLfHj ef JSgjdGJ JShjbjI aj GdCehGd GdYGdejI(B: (3h bO JdLC Edjg HMce GQJHGWgG HGdeUGdM GdCLfHjIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2009.s
(3HHdjhLQGajG(B: (3UaMGJ(B455 -480.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3YbhO GdCTZGd GdOhdjIs; (3GdefGbUI GdYGeI s; (3GdeeGQSI GdYGeIs; (3GdGJaGb GdeHGTQs; (3GdhSGWI s; (3GdJhajbs; (3GdJaGhVs; (3TQW GdJMcje ai EHQGe YbhO GdETZGd GdOhdjIs; (3YhGQV JfajP YbhO GdCTZGd GdOhdjIs; (3eTQhYjI TQW GdJMcje aj GdchjJs; (3NUhUjI TQW GdJMcje s; (3YbhO GdCTZGd GdOhdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2009